THE LEVEL OF VITAMIN D3 IN PATIENTS WITH TYPE 2 DIABETES, DEPENDING ON THE PRESENCE OF NON-ALCOHOLIC FATTY LIVER DISEASE - Udwan , M.B.; Kobylak , N.M.; Komisarenko , Y.I. (The Ukrainian Scientific Medical Youth Journal, 2018)
Introduction: Recently, vitamin D3 (cholecalciferol) deficiency has been considered as one of the factors for the development of type 2 diabetes mellitus (T2D) and metabolic syndrome (MS), which contributes to increased insulin resistance and reduced insulin secretion. The most pronounced vitamin D deficiency is observed in persons suffering from morbid obesity. The aim of this study was to assess the vitamin D3 status in patients with T2D, depending on the presence of non-alcoholic fatty liver disease (NAFLD).Materials and methods: The study included 69 patients with T2D. NAFLD was diagnosed with ultrasound examination. All patients were divided by us into 2 groups. The control group consisted of 29 patients with T2D without NAFLD. The main group included patients with T2D and concomitant NAFLD (n = 39). Student’s t-test was used for independent samples. In the analysis of qualitative variables, the criterion ⵼ 2 was used. The significance level was considered significant at p <0.05.Results: According to the obtained results, we observed significantly lower level of 25 (OH) D3 in patients with NAFLD compared with patients in the control group (28.25±12.67 vs. 19.9±8.67 ng/ml, p=0.002). Also, the presence of NAFLD in patients with T2DM associated with more pronounced metabolic disorders 25 (OH) D3. Vitamin 25 (OH) D3 deficiency in patients of the main group, which is determined, according to current recommendations, with a decrease in its level below 20ng/ml, was found in 73.5% of patients, which was significantly higher compared with the control group, where the deficiency was stated in 26.5% (p=0.014).Conclusions: Our study demonstrated that patients with T2D and NAFLD showed significantly lower level of 25 (OH) D3 compared with patients in the control group.